The use of online mathematics game for portfolio assessment of elementary school students - Ari Wibowo (STKIP PGRI Banjarmasin, 2020)
In this research, it is examined the use of online mathematics game for portfolio assessment of elementary school students. In the beginning of the study, it will be mapped the availability and the model of online mathematics game based on mathematics material of elementary school. Next, it will be examined the substance of self-evaluation and feedback that can be the basic for portfolio assessment. The research is classified into qualitative descriptive research with the source of the data is website reference that can be used to mathematics portfolio assessment of Elementary School students. The finding of the research is that one of the websites uses to mathematics portfolio assessment of Elementary School students is the use of online mathematics game. Now, one of online mathematics game containing self-evaluation and feedback is mathplayground.com. That site contains not less than 133 online mathematics game online for first until sixth grade students. The mathematics game daring materials are multiple diverse, containing number, geometry, measurement, and data display. In that online mathematics game, there is also material to self-evaluation and feedback that can be the base for teacher to portfolio assessment, that is the show of trophy and game certificate that can be printed. The show of trophy contains information about student quality in playing certain game, while certificate game as the evidence that student succeeds in finishing the game containing some levels.